Revitalisasi Ekosistem Qur'ani di Desa Sempu: Analisis Psiko-Spiritual Sinergi Lintas Generasi Melalui Pendekatan Asset-Based Community Development - Abd. Basith Arham; Putri Rosyadatun Najwa; Ahmad Nur Mufid (Lembaga Pengembangan Kinerja Dosen, 2025)
This community‑engagement study aimed to revitalize the Qur’anic ecosystem in Sempu Village (Ngancar District, Kediri Regency) by fostering inter‑generational synergy—among families, youth communities, and TPQ (Qur’an Study Groups)—using an asset‑based community development (ABCD) approach. The program identified and mobilised local assets such as TPQ students/alumni, active youth, community leaders, mosque/TPQ facilities, and locally established networks to strengthen Qur’an mentoring with a psycho‑spiritual dimension. The research employed a qualitative intervention method executed in three phases: asset mapping & diagnosis; design & implementation of the intervention; and program evaluation & reflection. Results indicated that youth attendance increased from 45 % to 78 %; the number of participating families rose from 18 to 32; and 90 % of TPQ administrators expressed the intention to continue the inter‑generational forum model on a regular basis. Discussion revealed that the intervention did more than improve attendance—it reinforced a sense of ownership, social connectedness, and internalization of Qur’anic values (spiritual well‑being). The psycho‑spiritual approach proved effective in strengthening youth identity and building a sustainable Qur’anic community culture. Limitations include the short duration of the intervention (12 weeks) and persistent communication barriers between generations related to time constraints and family workloads. Recommendations include conducting long‑term measurements, adapting the mentoring modules to accommodate family/youth time issues, and replicating the model in other villages with different characteristics.